Assessment of quality and accuracy of YouTube videos on percutaneous transthoracic biopsy - Gürkan, Okan; Gunduz, Canan (Journal of Surgery and Medicine, 2020)
Aim: YouTube is an essential source of medical information for patients, but may also be misleading, depending on the kind of content quality. The aim of this study is to evaluate the quality of YouTube videos on percutaneous transthoracic lung biopsy. Methods: A search on YouTube was performed with the terms ‘Lung Biopsy,’ ‘CT-Guided Lung Biopsy,’ ‘US-Guided Lung Biopsy,’ and ‘Percutaneous Transthoracic Biopsy.’ Relevant English videos were examined and scored by two reviewers. Video characteristics, uploaded sources, and content quality were assessed using different indices. Correlation analysis was conducted to investigate the possible correlation for global quality score. Results: Fifteen videos (47%) were uploaded by a healthcare professional, nine videos (28%) by a product company, six videos (19%) by an individual user, and 2 (6%) by an academic institution. The videos had a median (IQR) quality score of 2 (range 1-5), and a median (IQR) length of 235 (46-751) seconds. The quality of the videos varied, depending on the uploaded sources as well as whether they were uploaded by academic institutions, which had the highest quality. Some important components regarding the biopsy procedure, such as complications, were not evaluated in most videos. Conclusion: YouTube videos on percutaneous transthoracic lung biopsy (PTLB) had a low median content quality score, while some important points were grossly overlooked. Thus, YouTube videos may be a misleading source of patient information. Academic institutions and healthcare professionals should be creating accurate multimedia content for patients seeking informative medical information.